Epigenetic Pyrimidine Nucleotides in Competition with Natural dNTPs as Substrates for Diverse DNA Polymerases - Pospíšil, Šimon; Panattoni, Alessandro; Gracias, Filip; Sýkorová, Veronika; Hausnerová, Viola Vaňková; Vítovská, Dragana; Šanderová, Hana; Krásný, Libor; Hocek, Michal (ACS chemical biology, 2022)
Five 2'-deoxyribonucleoside triphosphates (dNTPs) derived from epigenetic pyrimidines (5-methylcytosine, 5-hydroxymethylcytosine, 5-formylcytosine, 5-hydroxymethyluracil, and 5-formyluracil) were prepared and systematically studied as substrates for nine DNA polymerases in competition with natural dNTPs by primer extension experiments. The incorporation of these substrates was evaluated by a restriction endonucleases cleavage-based assay and by a kinetic study of single nucleotide extension. All of the modified pyrimidine dNTPs were good substrates for the studied DNA polymerases that incorporated a significant percentage of the modified nucleotides into DNA even in the presence of natural nucleotides. 5-Methylcytosine dNTP was an even better substrate for most polymerases than natural dCTP. On the other hand, 5-hydroxymethyl-2'-deoxyuridine triphosphate was not the best substrate for SPO1 DNA polymerase, which naturally synthesizes 5hmU-rich genomes of the SPO1 bacteriophage. The results shed light onto the possibility of gene silencing through recycling and random incorporation of epigenetic nucleotides and into the replication of modified bacteriophage genomes.
Keywords: restrikční enzymy; DNA-Directed DNA Polymerase; Deoxyribonucleosides; 5-methylcytosin; epigeneze genetická; DNA; pyrimidinové nukleotidy; Nucleotides; DNA Restriction Enzymes; DNA-dependentní DNA-polymerasy; pyrimidiny; Pyrimidine Nucleotides; deoxyribonukleosidy; nukleotidy; Epigenesis, Genetic; 5-Methylcytosine; Pyrimidines